2019
DOI: 10.1038/s41477-019-0397-9
|View full text |Cite
|
Sign up to set email alerts
|

A domestication history of dynamic adaptation and genomic deterioration in Sorghum

Abstract: The evolution of domesticated cereals was a complex interaction of shifting selection pressures and repeated introgressions. Genomes of archaeological crops have the potential to reveal these dynamics without being obscured by recent breeding or introgression. We report a temporal series of archaeogenomes of the crop sorghum (Sorghum bicolor) from a single locality in Egyptian Nubia. These data indicate no evidence for the effects of a domestication bottleneck but instead suggest a steady decline in genetic di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 60 publications
4
83
2
1
Order By: Relevance
“…Evidence for reduced nucleotide diversity in landraces from a genetic bottleneck 5 or population size decline 14 has also been reported for sorghum.…”
Section: Main Textmentioning
confidence: 75%
See 1 more Smart Citation
“…Evidence for reduced nucleotide diversity in landraces from a genetic bottleneck 5 or population size decline 14 has also been reported for sorghum.…”
Section: Main Textmentioning
confidence: 75%
“…Additionally, Hamblin et al 32 showed that sorghum domestication is a complex process that might have included ancestral population structure, multiple domestication events, and/or introgressions from wild relatives. A recent study 14 has further shown that genetic load could have been reduced in modern lines by introgression with wild sorghum relatives. We hypothesize that the differences observed in load accumulation between maize and sorghum might be driven by both their different mating systems and domestication histories.…”
Section: Main Textmentioning
confidence: 99%
“…Genomic studies of ancient DNA are much less numerous in plants compared to animals remains [28-29], but have already provided fundamental insights into the process of domestication [24, [30][31][32][33][34]. The dynamic of this process is still debated and likely not the same in all species, but, as recently summarized [2], the consensus is that domestication was slow and gradual, and selected traits emerged at the cost of a decline in population size and genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…There are five landraces of sorghum (bicolor, kafir, guinea, caudatum, and durra) that are 100 classified based on morphology (Shehzad et al, 2009) and reflect different geographical 101 regions of adaptation (Price et al, 2005;Morris et al, 2013;Mace et al, 2013;Mullet et 102 al., 2014;Smith et al, 2019). There are also 10 intermediate landraces that are a 103 combination of the five landraces (Oliveira et al, 1996;Price et al, 2005).…”
Section: Plant Materials 99mentioning
confidence: 99%
“…Interpretation of these results within this phylogenetic context suggests that, 530 during further selection and improvement, salinity tolerance was lost in lineages that 531 were no longer subjected to continued environmental pressure. Lastly, given that S. 532 bicolor and especially the landrace durra (Smith et al, 2019) is known to be relatively 533 drought tolerant (Mullet et al, 2014;Fracasso et al, 2016;McCormick et al, 2018;Guo 534 et al, 2018) and, as with drought stress, salt stress has an initial osmotic component, we 535…”
mentioning
confidence: 98%